Heterophilic interference of rheumatoid factor in tsh immunometric assay: A cross-sectional observational study - Shaikh N Nayeemuddin; Akash Panigrahi; Rana Bhattacharjee; Subhankar Chowdhury (Indian Journal of Endocrinology and Metabolism, 2024)
Introduction: Considering the inherent vulnerability of immunoassays for heterophilic interference and the potential of Rheumatoid Factor (RF) to act as a heterophile-like antibody, we conducted this study to investigate if RF leads to any such heterophilic interference in seropositive rheumatoid arthritis (RA) patients. The study was done on the TSH assay as it is a noncompetitive, double antibody sandwich assay, which is known to be vulnerable to heterophilic interference. Methods: In this cross-sectional observational study, eighty-four consecutive newly diagnosed RF-positive RA patients underwent TSH, Free T4, and anti-TPO estimation using the chemiluminescence technique (CLIA) on Siemens Immulite 1000 platform. The samples were screened for TSH interference using four methods: 1) analysis on a different platform, 2) assessment of linearity using doubling dilutions, 3) polyethylene glycol (PEG) precipitation, and 4) addition of a commercial blocker. Results: Ten samples had a loss of linearity on serial dilution, indicating potential interference. After heterophile blocker treatment, five cases exhibited interference. One patient had diagnostic interpretation discordance on the second platform. No sample on PEG precipitation suggested the influence of antibodies. It is worth noting that even in cases where interference was suspected, the clinical interpretation was largely unaffected by the correction of TSH values based on mean dilution or measurement after heterophile blocker treatment. Conclusion: RF can cause heterophilic interference in TSH immunoassays used commercially. However, in most cases, this interference does not affect clinical decision-making.